2022
DOI: 10.3390/languages7010064
|View full text |Cite
|
Sign up to set email alerts
|

Overall, a Good Test, but…—Swedish Lower Secondary Teachers’ Perceptions and Use of National Test Results of English

Abstract: This article builds on a study set within the Swedish educational system and focuses on lower secondary teachers’ use of national test results when awarding final grades of English as a foreign language (EFL). In Sweden, teachers are entrusted with the responsibility of assessing their own students’ competences as well as assigning grades. To support them, there are compulsory national tests to be used as important advisory tools; however, they are not exams in a strict decisive sense. After a brief contextual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…Since the guidelines accompanying the tests serve an important function in standardizing the ratings done by a large and diverse group of teachers, this kind of teacher feedback is essential. As seen in this study and in Erickson and Tholin (forthcoming), teachers’ input on different aspects of test use also highlights system-related issues. Although these cannot be directly addressed in test development, the research findings contribute to ongoing policy discussions at the system level about the format, function and functionality of the national tests.…”
Section: Cooperation With the Main Stakeholderssupporting
confidence: 53%
See 2 more Smart Citations
“…Since the guidelines accompanying the tests serve an important function in standardizing the ratings done by a large and diverse group of teachers, this kind of teacher feedback is essential. As seen in this study and in Erickson and Tholin (forthcoming), teachers’ input on different aspects of test use also highlights system-related issues. Although these cannot be directly addressed in test development, the research findings contribute to ongoing policy discussions at the system level about the format, function and functionality of the national tests.…”
Section: Cooperation With the Main Stakeholderssupporting
confidence: 53%
“…Biggs, 1996), and that the intended curriculum is clarified in relation to the implemented curriculum (Van den Akker et al, 2003). Criticism obviously also occurs, however often focussing on system related issues, for example, workload and current regulations regarding national test results in relation to final grading (Borger, 2019b;Erickson & Tholin, forthcoming; see below).…”
Section: Contributions Of Teachersmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, most published research on the NTE (and other foreign languages) has originated from NAFS (2021), with an emphasis on the purpose and design of the tests. Erickson et al (2022) describe the collaborative nature of national tests, detailing the contributions made by the main stakeholders, the test-takers and teachers. Regarding the testtakers' feedback, this is considered essential, as 'students are the true experts, and […] test developers need their assistance to optimize the quality of the materials' (Erickson et al 2022: 8).…”
Section: Research Into the Ntementioning
confidence: 99%
“…Assessment standards have also been flagged, particularly for the year 6 test. In their study of teachers' perceptions of the year 6 writing component of the NTE, Erickson and Tholin (2022) found that teachers were critical of the level required, finding the assessment of the tests too lenient. This may account for the conflict between NTE grades and classroom assessment in year 6.…”
Section: Research Into the Ntementioning
confidence: 99%